Zahav home : cooking for friends & family - Solomonov, Michael; Cook, Steven (Restaurateur) (Harvest, an imprint of William Morrow, 2024)
"Award-winning chefs and bestselling authors of the James Beard Award-winning Zahav, Michael Solomonov and Steven Cook invite you to cook the way they do at home, with 125 new recipes for simple and achievable meals"--